The Relationship between Parents' Parenting Patterns and Smoking Incidents in Adolescents at SMP Negeri 4 Pekan Tolan, Kampung Rakyat District, South Labuhanbatu Regency in 2018 - Sri Misleini Saragih (Institute of Computer Science (IOCS), 2020)
The parenting style for children and adolescents is one of the factors that shape the behavior and character of a child. Parenting that is done properly by parents can have a positive influence on adolescents so that they do not smoke. 30% of Indonesians who smoke are reported to have started consuming cigarettes before they reach the age of 10. The purpose of this study is to identify parenting styles and the incidence of teenage smoking and to find out the relationship between parenting styles and the incidence of teenage smoking in SMP Negeri 4 Pekan Tolan, Kampung Rakyat District, Labuhanbatu Selatan Regency in 2018. The type of research used in this study is quantitative with a correlation research design. . The population amounted to 144 people, namely male students of SMP Negeri 4 Pekan Tolan in 2018. The research sample was 105 respondents, using purposive sampling technique. Data analysis used the chi-square test. The results showed that the majority permissive majority of adolescent parenting styles were 58 respondents (55.2%). The incidence of teenage smoking was 55 respondents (52.4%). The results of statistical analysis obtained p value 0.000 (p <0.05). This shows that Ha is accepted, which means that there is a relationship between parenting styles and the incidence of smoking at SMP Negeri 4 Pekan Tolan in 2018. Based on the results of this study, it can be concluded that there is a relationship between parenting styles and the incidence of smoking at SMP Negeri 4 Pekan Tolan in 2018. research places can provide warnings or health education on an ongoing basis about the dangers of smoking, so as to produce a healthy generation of the nation.